Synthetic ratiometric fluorescent probes for detection of ions. (21st November 2019) - Park, Sang-Hyun; Kwon, Nahyun; Lee, Jee-Hyeon; Yoon, Juyoung; Shin, Injae
Abstract : Synthetic ratiometric fluorescent probes are useful to detect metal cations and anions. Abstract : Metal cations and anions are essential for versatile physiological processes. Dysregulation of specific ion levels in living organisms is known to have an adverse effect on normal biological events. Owing to the pathophysiological significance of ions, sensitive and selective methods to detect these species in biological systems are in high demand. Because they can be used in methods for precise and quantitative analysis of ions, organic dye-based ratiometric fluorescent probes have been extensively explored in recent years. In this review, recent advances (2015–2019) made in the development and biological applications of synthetic ratiometric fluorescent probes are described. Particular emphasis is given to organic dye-based ratiometric fluorescent probes that are designed to detect biologically important and relevant ions in cells and living organisms. Also, the fundamental principles associated with the design of ratiometric fluorescent probes and perspectives about how to expand their biological applications are discussed.